2017
DOI: 10.1002/anie.201706304
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Primary Amine Catalysis for Asymmetric Mannich Reactions of Aldehydes with Ketimines: Stereoselectivity and Reactivity

Abstract: The application potential of primary amine catalysts in the context of Mannich reactions of aldehydes with ketimines is exemplified by isatin-derived ketimines and cyclic trifluoromethyl ketimines. Primary amine catalysts exhibit either unusual stereoselectivity or reactivity, which is not observable with secondary amine catalysts. Moreover, reversal of diastereofacial selectivity between primary and secondary amine catalysts is disclosed. These new reactions provide useful methods for the syntheses of chiral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 106 publications
0
26
0
Order By: Relevance
“…Excellent enantioselectivities were observed in the reactions of ketimine with a methyl group (entries 4,5 in Table 2), or an electron-donating group (entries 14, 15) at C-5, but a high level of enantioselection was maintained with halogens (entries 6-11) or hard electron-withdrawing substituents (entries 12,13). Excellent enantioselectivities were observed in the reactions of ketimine with a methyl group (entries 4,5 in Table 2), or an electron-donating group (entries 14, 15) at C-5, but a high level of enantioselection was maintained with halogens (entries 6-11) or hard electron-withdrawing substituents (entries 12,13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent enantioselectivities were observed in the reactions of ketimine with a methyl group (entries 4,5 in Table 2), or an electron-donating group (entries 14, 15) at C-5, but a high level of enantioselection was maintained with halogens (entries 6-11) or hard electron-withdrawing substituents (entries 12,13). Excellent enantioselectivities were observed in the reactions of ketimine with a methyl group (entries 4,5 in Table 2), or an electron-donating group (entries 14, 15) at C-5, but a high level of enantioselection was maintained with halogens (entries 6-11) or hard electron-withdrawing substituents (entries 12,13).…”
Section: Resultsmentioning
confidence: 99%
“…Good enantioselections were obtained by using chiral amines, [12] sulfonamides, [13] and both cinchona-derived thioureas [14] or squaramides. Good enantioselections were obtained by using chiral amines, [12] sulfonamides, [13] and both cinchona-derived thioureas [14] or squaramides.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Shao et al investigated the use of simple chiral primary amines to promote the enantioselective Mannich reaction of N- Boc-isatin imines 3 with aldehydes, such as acetaldehyde ( 15a ) [39]. When these reactions were catalyzed by simple chiral primary amine 16 in aqueous THF at 0 °C, they led to the corresponding chiral Mannich products 17 in good yields (74–81%) and uniformly excellent enantioselectivities (90–94% ee), as shown in Scheme 5.…”
Section: Reviewmentioning
confidence: 99%
“…By using another type of organocatalyst, such as L-diphenylprolinol trimethylsilyl ether 18 , these authors showed that a range of N- Cbz-isatin imines 19 reacted with α-substituted acetaldehydes 20 to give the corresponding chiral Mannich products 21 as major syn -diastereomers [39]. The latter were generally obtained with high syn / anti ratios (89:11 to 93:7) along with good yields (62–83%) and uniformly excellent enantioselectivities (92–99% ee), as shown in Scheme 6.…”
Section: Reviewmentioning
confidence: 99%
“…Indeed, the framework is a very promising precursor for the facile construction of 3‐aminopyrroloindoline towards the total synthesis of complex pyrroloindoline alkaloids (Figure ) . In accord with its medicinal relevancy, few fascinating indirect approaches have been well documented towards the catalytic asymmetric synthesis of 2‐oxoindolinyl‐ β 3, 3 ‐amino esters . Surprisingly, only two direct, elegant catalytic enantioselective approaches have been reported by Shibata et al.…”
Section: Introductionmentioning
confidence: 99%